‘Life Grasps Life’: Wilhelm Dilthey’s Minor Jurisprudence - Panu Minkkinen (Law Text Culture, 2017)
In an article from 1994, I tried to read Franz Kafka’s short story ’In the Penal Colony’ as what I called ’minor jurisprudence’ by drawing on an analogy from Gilles Deleuze and Félix Guattari. Whatever Kafka had to say about law should not, so I claimed, be understood as a form of theodicy as it usually is but, rather, as the possibility for a new ’politics of desire’. As ‘minor literature’, Kafka’s texts were inherently resistant to attempts to box them into conventional literary taxonomies. And it was this inherent resistance that created the opening for his ’minor jurisprudence’, as well. My aim will be to discuss the nature of this discordant force through the notion of vitalism. More specifically, I will discuss this vitalistic element through Wilhelm Dilthey’s 1883 treatise Introduction to the Human Sciences. But instead of focusing on the hermeneutical method which is the usual way in which Dilthey is introduced into the jurisprudential tradition, I will discuss his more general views on law as a cultural and political phenomenon and on jurisprudence as the ’human science’ that studies it, both significant themes in the 1883 Introduction but which scholarship has largely ignored.